PREDIKSI PROBABILITAS AUDIT DELAY DAN FAKTOR DETERMINANNYA (Proceeding Fakultas Ekonomi, 2013)
Time difference between financial statement and auditing opinion date indicates the amount of time needed in auditing settlement period. This condition can affect the punctuation of the information published and will influence market reaction toward the lenghty information. it will also the level of uncertainty based on the published information in the auditors financial statement in which containing company's profit information. This study aims to measure the factors which affect audit delay. They are total asset, operation loss and profit, auditors opinion, profitability, solvability and auditors reputation.The population of study in the manufactur companies registered in the Jakarta Stock Exchange in The Period of 2006-2009. Sampling Technique employed in this study is the purposive sampling with the total sample of 266 companies . the data analysis uses logistic regressions.The result of the study shows that the total asset and solvability have significat influence towar audit delay. on the aother hand, operation loss and profit and auditors opinion profitabulity and the auditors reputation do not have any influence toward audit delay.Keywords: audit delay, the size of the company, operation loss and profit, auditors opinion, profitability, solvability, auditors reputation.